2007
DOI: 10.1126/science.1141493
|View full text |Cite
|
Sign up to set email alerts
|

Explaining the Relation Between Birth Order and Intelligence

Abstract: T he interest in the relation between birth order and intelligence dates back to Sir Francis Galton's English Men of Science (1). Galton found more firstborn sons in prominent positions than what he attributed to chance. This was the start of numerous studies; one of the most influential was a Science publication in 1973 showing a negative association between birth order and intelligence in young Dutch men (2). Since then, sociologists, psychologists, and demographers have proposed several explanatory models (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
130
0
7

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(150 citation statements)
references
References 6 publications
13
130
0
7
Order By: Relevance
“…Since Galton (1874) elaborated on the superiority of the first born, and Adler (1870Adler ( -1937 developed a theory of how later borns vary in personality depending on family size, studies provide evidence that birth order is related to intelligence (e.g., Belmont & Marolla, 1973;Kristensen & Bjerkedal, 2007).…”
Section: Birth Order and Family Sizementioning
confidence: 99%
“…Since Galton (1874) elaborated on the superiority of the first born, and Adler (1870Adler ( -1937 developed a theory of how later borns vary in personality depending on family size, studies provide evidence that birth order is related to intelligence (e.g., Belmont & Marolla, 1973;Kristensen & Bjerkedal, 2007).…”
Section: Birth Order and Family Sizementioning
confidence: 99%
“…The data from these tests have been widely used and interpreted as IQ scores for research purposes (26)(27)(28)(29)(30)(31); in particular, the same Norwegian data figure prominently in the original research documenting the Flynn effect and are judged to be of particularly high quality and coverage (14). Further details on the IQ data and IQ trends in Norway at the time of the reform are available in SI Text.…”
Section: Datamentioning
confidence: 99%
“…To achieve this, entrepreneurial 3 individuals such as the self-employed have to assume and bear risk by making decisions, 4 often with incomplete information, about how to spend limited resources with no guarantee 5 of gain (Bhide, 2000). Subsequently, job fit studies have shown that adults select and remain 6 in self-employment because it fits in with their higher risk-taking propensity (Ekelund et al, However, one reason why research on self-employment determinants remains 14 incomplete is that there is insufficient attention given to how personality traits formed in 15 childhood inform and guide adult self-employment. This is surprising since childhood 16 clearly matters in developing occupational understandings (McGee & Stockard, 1991), and is Sulloway's born to rebel thesis, we posit that among families in which the parents have no 4 experience of self-employment that last-borns are more likely than their siblings to be self-5 employed in adulthood (Hypothesis 1).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, there are a number of reasons why 11 there may be countervailing effects that may either numb or run counter to Sulloway's born 12 to rebel thesis. Prevailing social conventions may promote primogeniture effects so that, 13 regardless of risk-taking propensities, first-borns are more likely to dutifully follow their 14 parents into business (Jimenez, 2009). Another reason is that for last-borns that grow up in 15 familial business contexts, these contexts are the social norm, suggesting that self-16 employment is both familiar and normal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation